Sistem Informasi Kepegawaian Berbasis Website Pada PT Sumatera Panca Rajo Palembang - Ega Dwisaputra Nurmawan; Mulyati Mulyati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
The current information system is something that is needed by all forms of business. This has an impact on significant technological developments, so companies are competing to provide the best service by increasing the use of technology and information systems. In the daily operations of PT. Sumatra Panca Rajo currently only uses ordinary office applications yet to implement a staffing system, this makes it difficult to perform absenteeism and overtime data recapitulation because it still uses paper stored in folders, making it vulnerable to loss and damage. To do attendance data recording and overtime, usually the operational part must look for archived data first. That's why the management of PT. Sumatra Panca Rajo has difficulty controlling, and evaluating the performance of its employees, this problem is perceived as hampering the company's performance. Based on the description, the author tries to help solve the problem by creating a Website Based Personnel Information System at PT. Sumatra Panca Rajo. In developing this information system the author uses the development of Iteration software, to analyze the problem the author uses the PIECES analysis flow, collecting data through observation, interviews, and literature. Designing software using UML modeling. With the construction of this information system PT. Sumatra Panca Rajo can obtain information about attendance, employee data, transfer, employee dismissal, and employee recruitment, and can evaluate the performance of its employees.